PENETAPAN KADAR Pb PADA SHAMPOO BERBAGAI MERK DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Farida Jaya; Any Guntarti; Zainul Kamal (Pharmaciana, 2013)
The source of lead pollution (Pb) can come from cosmetic product including shampoo. The purpose of thisresearch are to know wether there is Pb in the shampoo cosmetic based on different brands and colours of theshampoo. The sample of the shampoos that used in this research are A, B, C, and D. Each of the samples replicated5 times, then analyzed with atomic absorbtion specktrophotometry. Then, one of the sample are taken from onebrand with different colour and replicated 5 times. The result of this research shows that from the different brandof shampoos contain Pb. The average level of Pb that obtained from analysis are, brand A (0,4838 ppm 0,0538ppm), brand B (0,6935 ppm 0,3131 ppm), brand C (0,8354 ppm 0,0405 ppm), and brand D ( 0,9517 ppm0,0811 ppm). Whereas for the same shampoo brand but different in colour had average level of Pb: shampoo I (redcolour)= (0,5428 0,0192) ppm, Shampoo II (yellow colour) = (0,3606 0,0255) ppm, Shampoo III (blue colour)= (0,4385 0,0062) ppm, and Shampoo IV (green colour) = (0,1427 0,0133) ppm.